Exogenous and Endogenous Phosphoethanolamine Transferases Differently Affect Colistin Resistance and Fitness in Pseudomonas aeruginosa - Cervoni, Matteo; Lo Sciuto, Alessandra; Bianchini, Chiara; Mancone, Carmine; Imperi, Francesco (Frontiers in Microbiology, 2021)
Colistin represents a last-line treatment option for infections caused by multidrug resistant Gram-negative pathogens, including Pseudomonas aeruginosa. Colistin resistance generally involves the modification of the lipid A moiety of LPS with positively charged molecules, namely phosphoethanolamine (PEtN) or 4-amino-4-deoxy-L-arabinose (Ara4N), that reduce colistin affinity for its target. Several lines of evidence highlighted lipid A aminoarabinosylation as the primary colistin resistance mechanism in P. aeruginosa, while the contribution of phosphoethanolamination remains elusive. PEtN modification can be due to either endogenous (chromosomally encoded) PEtN transferase(s) (e.g., EptA in P. aeruginosa) or plasmid borne MCR enzymes, commonly found in enterobacteria. By individually cloning eptA and mcr-1 into a plasmid for inducible gene expression, we demonstrated that MCR-1 and EptA have comparable PEtN transferase activity in P. aeruginosa and confer colistin resistance levels similar to those provided by lipid A aminoarabinosylation. Notably, EptA, but not MCR-1, negatively affects P. aeruginosa growth and, to a lesser extent, cell envelope integrity when expressed at high levels. Mutagenesis experiments revealed that PEtN transferase activity does not account for the noxious effects of EptA overexpression, that instead requires a C-terminal tail unique to P. aeruginosa EptA, whose function remains unknown. Overall, this study shows that both endogenous and exogenous PEtN transferases can promote colistin resistance in P. aeruginosa, and that PEtN and MCR-1 mediated resistance has no impact on growth and cell envelope homeostasis, suggesting that there may be no fitness barriers to the spread of mcr-1 in P. aeruginosa.